2019
DOI: 10.1002/chem.201902017
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselectivity Induced by Stereoselective Interlocking: A Novel Core Motif for Tropos Ligands

Abstract: Well-defineds upramolecular interactions are a powerful tool to control the stereochemistry of acatalytic reaction.I nt his paper,w er eport an ovel core motif for fluxional 2,2'-biphenyl ligands carrying (S)-amino acid-derived interaction sites in 5,5'-position that cause spontaneous enrichment of the R ax rotamer.T he process is based on strong non-covalenti nterlocking between interaction sites, which causes diastereoselective formation of as upramolecular ligand dimer,i nw hich the axial chirality of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The investigated ligand design was found to trigger a process of spontaneous rotamer enrichment of the Ra isomer for all compounds (see Figure 7). [49][50][51][52] Comprehensive structural investigations revealed that the enrichment process is based on intermolecular interlocking of selector groups that entails the formation of highly-ordered ligand dimers. The point chirality of the amino acid-based selector units causes spatial confinement during this interaction, so that only the Ra rotamers can dimerize.…”
Section: R'mentioning
confidence: 99%
See 1 more Smart Citation
“…The investigated ligand design was found to trigger a process of spontaneous rotamer enrichment of the Ra isomer for all compounds (see Figure 7). [49][50][51][52] Comprehensive structural investigations revealed that the enrichment process is based on intermolecular interlocking of selector groups that entails the formation of highly-ordered ligand dimers. The point chirality of the amino acid-based selector units causes spatial confinement during this interaction, so that only the Ra rotamers can dimerize.…”
Section: R'mentioning
confidence: 99%
“…Similar to the previous examples, 30 this distribution of rotamers could be selectively shifted to either side by equilibrating the ligand in presence of an appropriate additive that would occupy the ligand's binding sites (vide infra). 50 The self-induced chirality transfer was found to produce potent ligands for enantioselective transformations. Biphenol ligands 13a-c were used in titanium-mediated enantioselective alkylation reactions of aromatic aldehydes with diethyl zinc and a range of alcohols were formed with enantioselectivitites of up to 10:90 (S:R).…”
Section: R'mentioning
confidence: 99%
“…In addition to cofactor‐controlled enantioselective catalysis developed and investigated by Reek and Moberg [31–33] and helical assembly developed by Raynal [34][35] , Breit and co‐workers successfully prepared supramolecular amino acid‐based PhanePhos [36] and DNA base pair‐inspired dynamic ligands (see Figure 1). [8] In recent years we achieved very good catalytic selectivities and interesting catalyst properties with flexible biphenyl ligands, [37] i. e ., temperature‐controlled enantioselectivity, [38] enantioselective self‐amplification by non‐covalent product‐catalyst interactions [39–43] and supramolecular interlocking [44–46] . In continuation of these efforts, we present here the synthesis and characterization of the stereodynamic behavior of a 2,2’‐biphenol‐based dianilino ligand bridged by a chiral l ‐tartaric acid unit in the ligand backbone.…”
Section: Introductionmentioning
confidence: 98%
“…l ‐Valine and l ‐proline derived selectors for stereodynamic biphenyls were introduced by Trapp and coworkers in self‐amplifying supramolecular catalysts [23–32] and were originally developed as enantioselective selectors [33] in chiral stationary phases for chiral GC, i. e. Chirasil ‐Val, [34,35] and proline‐based chiral stationary phases developed by Pirkle et al . for chiral HPLC [36,37] …”
Section: Introductionmentioning
confidence: 99%